THE ROLE OF INFORMATION TECHNOLOGY IN IMPROVING BUSINESS PROCESS EFFICIENCY IN THE ERA OF ARTIFICIAL INTELLIGENCE - Kohar, Abdul (Jurnal Jembatan Efektivitas Ilmu dan Akhlak Ahlussunah Wal Jama’ah, 2025)
The advancement of Information Technology (IT) and its integration with Artificial Intelligence (AI) has brought about a major transformation in the modern business world. This study aims to comprehensively examine the role of IT and AI in improving business process efficiency, using a literature study approach and global case analysis. The results of the study show that the implementation of AI-based IT systems can automate routine processes, accelerate decision-making, and improve service accuracy. Case studies from companies such as Amazon, Siemens, and JP Morgan Chase show significant operational time savings, cost reductions, and increased customer satisfaction. The discussion also covers implementation challenges such as infrastructure readiness, data quality, and HR competency. This study recommends a gradual strategy in technology adoption, strengthening digital literacy, and an ethical approach in utilizing AI to ensure sustainable efficiency. These findings can be a strategic reference for organizations that want to accelerate digital transformation and increase competitiveness in the industrial era 4.0.